Economic specialization and diversification at the country and regional level: introducing a conceptual framework to study innovation policy logics. Issue 12 (2nd December 2018) - Cai, Yuzhuo; Normann, Roger; Pinheiro, Rómulo; Sotarauta, Markku
ABSTRACT: While there has been a shared understanding that innovation policy is about rendering institutional change, there has been an emerging interest in identifying the institutional logics underlying innovation policy. To date, few studies have attempted to conceptualise these logics. This paper develops a novel conceptual framework for understanding innovation policy logics based on seminal contributions from organizational and economic theory. The framework distinguishes four logics, namely, specialized exploitation, diversified exploitation, specialized exploration, and diversified exploration. It is illustrated in the empirical analysis of innovation policies and development on both national and regional levels in Norway and Finland. The findings reveal that in both countries there is a movement towards increasingly diversified innovation strategies, despite differences in logics underpinning the policies.